Empires of the word : a language history of the world - Ostler, Nicholas (HarperPerennial, 2006)
This text offers a 'natural history of languages' that recounts the ways in which one language has superseded another at different times in history. It shows that the language of the future will, like the languages of the past, be full of surprises.